Demographic, Transition, and Vocational Rehabilitation Service Variables' Association With High School Completion Outcomes of Youth With Disabilities Receiving SSI. (October 2021) - Iwanaga, Kanako; Chan, Fong; Anderson, Catherine A.; Ditchman, Nicole; Kaya, Cahit; Hartman, Ellie; Tansey, Timothy N.
Completing high school expands career prospects for young adults with disabilities, increasing their likelihood for gainful employment. Those who graduate from high school are more likely to have higher salaries and longer job tenure than those who do not have high school diplomas. As such, graduating from high school is a significant milestone for students with disabilities. Yet, the specific predictors of high school completion among youth with disabilities are not well understood. This study used three multiple logistic regression analyses and a hierarchical logistic regression analysis to evaluate demographic, PROMISE transition services, and vocational rehabilitation (VR) services as predictors of high school completion in a sample of 350 transition-age youth receiving Supplemental Security Income. Among the demographic variables examined, race, disability type, parent education, and family income were significant predictors of completion. For transition services, social skills training and self-advocacy training were independently associated with high school completion, while miscellaneous training was the only independent significant VR service predictor. Findings support the importance of pre-employment transition services, especially in the areas of social skills training, self-advocacy training, and VR services in the areas of miscellaneous training that can be used to promote completion of high school.